FORMULATION AND CHARACTERIZATION OF POLY-HERBAL CREAM FOR THE TREATMENT OF HYPERPIGMENTATION - Ankita S. Bhavsar
Melanin is responsible for skin color. Hyperpigmentation, characterized by excessive darkening of the skin, may cause significant cosmetic issues and impact quality of life. Exposure to ultraviolet radiation has led to widespread photo-aging across all skin types. Through their interaction with endogenous photosensitizers, ultraviolet rays produce reactive oxygen species and free radicals and causing cumulative structural and physiological damage to skin. This results in sunburn, wrinkles, hyperpigmentation and skin cancer. Topical antioxidants may protect the skin from environmental damage. Certain plant extracts have shown promising antioxidant and anti-melanogenic properties. Therefore, the current study was conducted to formulate and evaluate effectiveness of herbal cream containing extracts of liquorice, ginseng and amla. Among the eight batches tested, batch F3 containing amla (0.5%), liquorice (3%) and ginseng (2%) demonstrated excellent homogeneity, washability, spreadability and pH, along with outstanding free radical scavenging activity (85.9%) and stability. Moreover, positive results of the patch test indicate the safety of the formulation.